Should green governments give priority to environmental policies over growth-enhancing policies? - George Economides; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper studies the properties of second-best optimal policy in a standard general equilibrium model of growth augmented with renewable natural resources. The government chooses its policy instruments (the income tax rate and the allocation of collected tax revenues between public investment and environmental policy) to solve a Ramsey-type policy problem. The main result is that, the more the citizens care about the environment, the more growth-enhancing policies the government finds it optimal to choose in the long run. This is because when citizens care about the environment, this requires tax revenues for environmental policy and can be only achieved by large tax bases and high growth. Thus, only growing economies can afford to care about the environment. This is the case even if pollution occurs as a by-product of output produced.
Keywords: H23; O13; Q2; 330; second-best policy; natural resources; economic growth; Umweltpolitik; Wachstumspolitik; Second Best; Allgemeines Gleichgewicht; Erneuerbare Ressourcen; Theorie